EVALUATION OF DIGITAL MARKETING EFFECTIVENESS TO IMPROVING SALES PERFORMANCE AT PT MUTIARA BENIH NUSANTARA - Sari, Intan Lukita; Setiyani, Rahmawati; Rahyunanto, Setyo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study aims to analyze the factors that influence digital marketing of PT Mutiara Benih Nusantara, determine the level of effectiveness of Shopee and TikTok ecommerce, and analyze the most effective e-commerce platform. The variables analyzed in this study are Shopee and TikTok. Shopee and TikTok were chosen because both are platforms that have the same marketing strategy, but sales data shows a difference in the total number of product orders sold on both platforms. The analysis method used is multiple linear regression analysis, normality test, ttest by using primary data on PT Mutiara Benih Nusantara product sales and distributing questionnaires to the relevant employees. The results of the study indicate that the factors that influence the effectiveness of digital marketing on Shopee and TikTok PT Mutiara Benih Nusantara are features and content. Shopee and TikTok have the same statistical significance in improving PT Mutiara Benih Nusantara's sales performance. The e-commerce platform that is quite effective is TikTok e-commerce. These findings emphasize the importance of selecting a digital marketing strategy. However, these aspects were not analyzed further in this study because the focus of the study was directed at evaluating the effectiveness of using the Shopee and TikTok Shop platforms as digital marketing tools